2021
DOI: 10.7759/cureus.15006
|View full text |Cite
|
Sign up to set email alerts
|

Triple-Negative Metaplastic Breast Carcinoma: Association of Epidermal Growth Factor Receptor Expression With Prognostic Parameters and Clinical Outcome

Abstract: IntroductionMetaplastic breast carcinoma (MBC) is one of the rare special subtypes of breast carcinoma associated with poor prognostic features compared with invasive ductal carcinoma. Moreover, therapeutic options are limited in MBC owing to frequent triple-negative profiles of these tumors. Epidermal growth factor receptor (EGFR) is a proto-oncogene that is overexpressed in many human cancers, and is a potential therapeutic target. Therefore, in this study, we evaluated the expression of EGFR in MBC by immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
1
1
Order By: Relevance
“…These results were similar to our research hence EGFR overexpression can be used as a prognostic tool to predict the invasive nature of the tumor which can lead to poor prognosis. 12 Contrary to the high expression of EGFR in our study another regional study concluded that EGFR overexpression was observed in only 2.7% of the cases with TNBC which may be due to underlying genetic alterations. 13 In our study the mean age of the patients diagnosed with TNBC was 46.27 ± 3.75 years as compared to 46.26 ± 12.22 years in an observational study conducted in Pakistan.…”
Section: Discussioncontrasting
confidence: 97%
“…These results were similar to our research hence EGFR overexpression can be used as a prognostic tool to predict the invasive nature of the tumor which can lead to poor prognosis. 12 Contrary to the high expression of EGFR in our study another regional study concluded that EGFR overexpression was observed in only 2.7% of the cases with TNBC which may be due to underlying genetic alterations. 13 In our study the mean age of the patients diagnosed with TNBC was 46.27 ± 3.75 years as compared to 46.26 ± 12.22 years in an observational study conducted in Pakistan.…”
Section: Discussioncontrasting
confidence: 97%
“…Hematoxylin and eosin (H&E)-stained slides of all cases were retrieved and diagnoses were reviewed. Moreover, ER, PR and HER2/neu immunohistochemical studies were performed to confirm the triple-negative status, as described in previous studies [6][7][8][9][10]. Cytokeratin 5/6 (CK5/6) was performed to subtype triple-negative MBCs into basal and non-basal subtypes.…”
Section: Methodsmentioning
confidence: 99%